Benefit Sharing in Protected Area Management : The Case of Tarangire National Park, Tanzania - Clark, Carrie; Davenport, Lisa; Mkanga, Paul (World Bank, Washington, DC, 2012)
Conservation is often viewed as a tradeoff between the development of short-term benefits and protection for long-term benefits. However, with the appropriate mechanisms, it is possible to achieve both aims. The justification to protect parks in developing countries can be based on an economic rationale rather than a primarily social or environmental one. Enhancing the revenue earning potential of protected areas from tourism, and directly returning those benefits to the appropriate set of stakeholders can result in a balanced approach to long-term environmental conservation and short-term economic development. Currently, approximately 14 percent of Tanzanian territory is designated as protected areas. Though national parks, game preserves, and other protected areas have generated revenue for the government, not much of this revenue has been retained to enhance the conservation efforts in these areas or to compensate the local communities. Funding for the Tarangire National Park (TNP) as it is for the Tanzania National Parks Authority (TANAPA), the national park authority, is limited and gate revenues are supplemented by external donors, both through TANAPA and directly to TNP. Within TNP, actual revenues have consistently been greater than expenditures since the 1991 financial year. TNP operates at a profit which has increased variably by approximately 23 percent to 140 percent per year. Surplus revenues are contributed to TANAPA.